Dealing with Increased Risk of Natural Disasters : Challenges and Options - Keen, Michael (IMF Working Papers; Working Paper, 2003)
Natural disaster risk is emerging as an increasingly important constraint on economic development and poverty reduction. This paper first sets out the key stylized facts in the area-that the costs of disaster have been increasing, seem set to continue to increase, and bear especially heavily on the poorest. It then reviews the key economic issues at stake, focusing in particular on the actual and prospective roles of, and interaction between, market instruments and public interventions in dealing with disaster risk. Key sources of market failure include the difficulty of risk spreading and, perhaps even more fundamental, the Samaritan's dilemma: the underinvestment in protective measures associated with the rational expectation that others will provide support if disaster occurs. Innovations addressing each of these are discussed.